Cost-Return Budgets — Nonirrigated Crops - Langemeier, Larry N.; Whitney, David A.; Sloderbeck, Phillip E.; Fjell, Dale L.; Peterson, Dallas (My University, 1997)
This publication uses specific input values and rates for seed, insecticide, herbicide, and fertilizer based on a given yield level to provide information for producers with nonirrigated crops.
MF941_1997_10
Keywords: MF942; Economics; Crops; MF